Analisis Keandalan Sistem Jaringan Distribusi Di Gardu Induk Bringin Penyulang Brg-2 Pt. Pln (Persero) Ul Salatiga Dengan Metode Section Technique - Wahyudi Ragil, Ragil, Umar, S.T., M.T (2016)
Electrical energy has been become a very important requirement for people in this day, therefore continuity in the distribution of electrical energy is absolutely necessary. A power distribution network system can be said to be reliable if the interruption and outages that occurred within one year lower than the figures specified reliability index. One of the ways used to calculate the reliability index of the electricity distribution network is the method section technique. Reliability index which will be calculated is SAIFI, SAIDI, and CAIDI. In this research, calculation of reliability index in the distribution network BRG-2 feeder. BRG-2 feeder is one the feeders in Bringin substations who are in the working area of PT. PLN (Persero). After calculation, the reliability index of the BRG-2 feeder be obtained that SAIFI 8.65454469 failure/year, SAIDI 26.11252417 hour/year and CAIDI CAIDI 3.01720369 hour/year. To determine the index has been calculated included the category of reliable or not, than need to be compared with standard issued by PT. PLN (Persero) in SPLN 68-2 : 1986 that the SAIFI was 3.2 failure/year and SAIDI 21 hour/year. It can be seen that BRG-2 feeder distribution networknot reliable because the value of SAIFI and SAIDI exceed the standards set.